Pengaruh Penerapan Sistem Persediaan Perpetual Terhadap Efisiensi Persediaan dan Laba Perusahaan Dagang - Fadhila Supari; Lasmi Yupita; Widya Febriani; Ulia Ulfa; Miftahul Hasanah (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
In the business world, proper inventory management plays a vital role in sustaining operations and ensuring the profitability of trading companies. This study examines the effect of implementing a perpetual inventory system on stock management efficiency and profit growth. A quantitative approach was applied using a survey method, with multiple linear regression analysis based on financial statement data collected over a five-year period. The findings reveal a positive and significant influence, where a regression coefficient of 0.35 indicates improved inventory efficiency, while a coefficient of 0.45 reflects increased profitability. The system enables real-time stock monitoring, minimizes the risk of overstocking or stockouts, and facilitates timely purchasing adjustments in line with market demand. Based on these results, the perpetual inventory system is recommended as a management strategy capable of enhancing both operational efficiency and the profitability of trading companies..